2018
DOI: 10.1002/chem.201800981
|View full text |Cite
|
Sign up to set email alerts
|

Gold(III) Complexes for Antitumor Applications: An Overview

Abstract: Gold(III) complexes have emerged as a versatile and effective class of metal-based anticancer agents. The development of various types of ligands capable of stabilizing the Au cation and preventing its reduction under physiological conditions, such as chelating nitrogen-donors, dithiocarbamates and C^N cyclometalled ligands, has opened the way for the exploration of their potential intracellular targets and action mechanisms. At the same time, the bioconjugation of Au complexes has emerged as a promising strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
112
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 129 publications
1
112
0
Order By: Relevance
“…All three classes of the newly synthesized cationic and neutral gold(I) and gold(III)‐isothiourea complexes were next examined in some preliminary biological studies . Some significant results are provided below, with full details available in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…All three classes of the newly synthesized cationic and neutral gold(I) and gold(III)‐isothiourea complexes were next examined in some preliminary biological studies . Some significant results are provided below, with full details available in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of our exploration of gold(III) chemistry [20,21] we found that the nature of cyclometallated ligands had ap ro-found effect on the thermals tabilityo fp otentially labile complexes. For example, whereas the Au III alkene complex [Me 2 Au(COD)] + could only be isolated and crystallized at low temperatures, [22] analogous complexes [(C^C)Au(COD)] + supported by chelating biscarbanionic biphenylyl insteado f methyl ligands provedt ob et hermally stable (COD = 1,5-cyclooctadiene;ĈC = 4,4'-di-tert-butylbiphenyl-2,2'-diyl).…”
Section: Introductionmentioning
confidence: 99%
“…of cisplatin and its second‐generation antitumor drugs (carboplatin and oxaliplatin) encouraged the researchers to focus on new isoelectronic and isostructural analogues of metal ions other than Pt(II). The chemistry of Au(III) received interest fortified by their outstanding cytotoxicity against cisplatin resistant cell lines, and antimicrobial activity against the biofilm mediated infections having resistance to antibiotics The anticancer activity of Au(III) complexes incorporating either N‐donor, dithiocarbamate or C ^ N cyclometalated ligands has been reported . However, Au(III) complexes have fast rate of hydrolysis and high reduction potential to be reduced with the cellular reductants (e.g.…”
Section: Introductionmentioning
confidence: 99%